Anabolic effects of acellular bone marrow, platelet rich plasma, and serum on equine suspensory ligament fibroblasts in vitro - Smith, J. J.; Ross, M. W.; Smith, R. K. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
The purpose of this study was to investigate the response of suspensory ligament fibroblasts (SLF) to in vitro stimulation using acellular bone marrow (ABM), platelet rich plasma (in vitro PRP), and serum as potential treatment modalities for suspensory desmitis. Blood, bone marrow, and suspensory ligaments were collected from five horses. SLF were harvested, grown until confluent, and stimulated with various concentrations of ABM, PRP, equine serum, foetal bovine serum, and medium (control). The responses to the treatments were assessed using a combination of radiolabeling for total protein synthesis and an ELISA for quantification of Cartilage Oligomeric Matrix Protein (COMP) production. Addition of all of the samples resulted in significant increases in COMP and total protein synthesis over controls (P<0.001). ABM caused the greatest increase in both COMP and total protein synthesis by the SLF. Equine ABM, PRP, and serum contain anabolic factors that promote matrix synthesis by SLF in vitro, with ABM having the greatest effect. Application of bone marrow to injured ligaments may enhance healing by providing anabolic factors, other than or in addition to mesenchymal stem cells, which stimulate matrix production.
Keywords: Bone marrow aspirate; platelet rich plasma; serum; growth factor; suspensory desmitis.